2018
DOI: 10.1111/cfs.12583
|View full text |Cite
|
Sign up to set email alerts
|

Supporting foster and kinship carers to promote the mental health of children

Abstract: The majority of children and young people removed from the care of their parents by the state of Victoria, Australia, reside in foster or kinship care. These children have experienced a broad range of adverse conditions and are up to 4 times more likely to experience problems with mental health than their mainstream peers. This paper draws on the perspectives of foster and kinship carers, describing the disconnection between their role as mental health advocates and their interest in early intervention in a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In contrast to the perceptions of foster and kinship carers (Fergeus et al, 2019), practitioners across all sectors readily identified the importance of caregiver wellbeing to young people's mental health outcomes. Involving caregivers of young people in OoHC is likely to increase young people's retention in treatment (Dorsey et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast to the perceptions of foster and kinship carers (Fergeus et al, 2019), practitioners across all sectors readily identified the importance of caregiver wellbeing to young people's mental health outcomes. Involving caregivers of young people in OoHC is likely to increase young people's retention in treatment (Dorsey et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…We acknowledge the importance of young people in OoHC as central to decision‐making about their own treatment and care (Davies & Wright, 2008). We have described elsewhere our initiatives to include young people (Herrman et al, 2016; Monson et al, 2019; Rafeld et al, 2019) and carers (Fergeus et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of our study indicate that, for foster carers, children's externalising with mental health problems (Fergeus et al, 2019), because if these problems are not adequately addressed, they could worsen and/or lead to placement breakdown (Hiller et al, 2020;Vanderfaeillie et al, 2018aVanderfaeillie et al, , 2018b. Such programmes could also alleviate the strain on carers, thus reinforcing their parenting abilities (Lipscombe et al, 2004).…”
Section: Supporting Carers In Dealing With Difficult Behaviour Of Childrenmentioning
confidence: 81%
“…In contrast to the findings of , the findings of this study did not unambiguously endorse the Dutch practice of cultural matching for foster placements of unaccompanied refugee children. Although (Fergeus et al, 2019) because these problems, if not adequately addressed, could worsen and/or lead to placement breakdowns (Hiller et al, 2020;Vanderfaeillie et al, 2018aVanderfaeillie et al, , 2018b. Such programmes could also alleviate the strain on carers, thus reinforcing their parenting abilities (Lipscombe et al, 2004).…”
Section: Implications For Research Policy and Practicementioning
confidence: 99%